The dramatic monologue: between lyrics and fiction - Sabadell Nieto, Juana (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Given its qualities as a hyhrid genre, the dramatie monologue forces one to rethink the problematic of subjectivity in lyric poems, and offers the possibility of analyzing the lyric from narratological perspectives. Moreover, it leads to a consideration of the differing degrees of dramatic realization in lyric texts, and reopens the question of the limits between literary genres. This article highlights some of the constitutive aspects of this literary artifice, in order to stimulate the interest of Spanish criticism in this poetic form.